Perbaikan ALTERNATIF LONGSORAN DENGAN METODE PRELOADING DI JALAN LINGKAR TUBAN - Reva Ayundasari Ayundasari; Laily Endah Fatmawati; Nurani Hartatik; Herry Widhiarto; Yudi D. Prasetyo; Siska Yovina Ervitasari (LPPM Universitas Abdurrab, 2022)
The construction of the Tuban Ring Road Project or the so-called Ring Road/Tuban Ring Road is included in the Semanding District, located in Tuban Regency. This area is a potential road access because the road is the main access connecting the city of Tuban and the city of Lamongan. In field conditions at STA 9+050 to STA 9+075, there is land subsidence due to the additional load on the original soil. A soil improvement is needed to overcome the problem of subsidence in these conditions. Based on the conditions described, the Prefabricated Vertical Drain (PVD) method can be used as an alternative to soil improvement on the Tuban Ring Road. So the embankment height is 1.50 m. The length of time for land subsidence without using PVD is 197.311 years. Then after using PVD, the distance and depth of PVD installation is obtained, namely a triangular pattern with an installation distance of 1 m, it takes 12.5 weeks.